2013
DOI: 10.1155/2013/930673
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Contractile Reserve Parameters Are Related to Prognosis in Septic Shock

Abstract: Introduction. Cardiac reserve could be defined as the spontaneous magnitude from basal to maximal cardiac power under stress conditions. The aim of this study was to evaluate the prognostic value of cardiac reserve parameters in resuscitated septic shock patients. Methods. Seventy patients with septic shock were included in a prospective and observational study. Prior to inclusion, patients were resuscitated to reach a mean arterial pressure of 65–75 mmHg with an euvolemic status. General, hemodynamic, and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Detailed journal article demographics, outcomes, and disease state definitions of the condition examined are highlighted in Table 3 . In the final analysis, 41 studies [ 3 , 6 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] were included covering a total of 33,906 patients. When determining the use of CP in the determination of prognosis throughout the various disease processes, we categorized the articles based on the disease process they were associated with, as shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed journal article demographics, outcomes, and disease state definitions of the condition examined are highlighted in Table 3 . In the final analysis, 41 studies [ 3 , 6 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] were included covering a total of 33,906 patients. When determining the use of CP in the determination of prognosis throughout the various disease processes, we categorized the articles based on the disease process they were associated with, as shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…This group contained three articles, where all three articles compared CPI between survivors and non-survivors and had slightly different definitions of septic shock, shown in Table 3 . One study showed a very strong significance ( p < 0.0001) with a population size of 39 [ 23 ]; another showed just under statistical significance between groups with p = 0.058 with a population size of 70 [ 17 ]; and the third article, which had a population size of 141, showed no statistical significance with p > 0.05 [ 18 ]. One article also tested the significance of CPO in determining mortality in septic shock and compared ICU survivors and non-survivors with a significant finding of p < 0.0001 [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the dobutamine challenge test to evaluate the regulatory capacity of the β-adrenergic system in septic patients was introduced by Vallet and co-workers, who were able to predict survival in septic patients by measuring the response to oxygen delivery, consumption, and extraction [ 20 ]. A nonpharmacological version of the dobutamine stress test was explored by Kimmoun et al to assess the efficiency of cardiac adaptation to septic shock by measuring cardiac contractility reserve-related parameters, including cardiac index, double product, and cardiac power index during the resuscitation procedure [ 21 ]. In this context, the heart rate response is also a promising methodology to assess the ability of the autonomic nervous system to regulate cardiovascular responses and assess interorgan communication [ 22 , 23 ].…”
Section: Pillar Ii: Organ Functionmentioning
confidence: 99%
“…Septic shock, the most severe form of sepsis, is highly complex, with concurrent myocardial, vascular (macro- and micro-), tissue perfusion and cellular level abnormalities. Myocardial abnormalities include both cardiomyocyte injury [ 4 ] and structural myocardial dysfunction [ 6 , 7 ]. Vascular abnormalities affect the endothelium, sub-endothelial tissues, microcirculation and vasomotor tone.…”
Section: Introductionmentioning
confidence: 99%